Entrepreneurship Study Group Education: Juvenile Delinquency Prevention Program through Entrepreneurship Formation Using Social Media in Turida Village, Mataram City - Triana Lidona Aprilani; Laili Hurriati; Mimi Cahayani; Sri Karyati (Experimental Student Experiences, 2024)
The specific objectives of implementing this PkM activity are: (1) Forming study groups among youth in making animation, (2) Providing input, insight, and knowledge about youth, (3) Reducing the level of juvenile delinquency which continues to increase from year to year, and (4) Equipping youth with entrepreneurial skills by using social media to reduce their free time. For the sake of the continuity of this community service activity, a method that can be digested and absorbed directly by the sons and daughters of teenagers in Turida Babakan Village, Mataram City, namely; The "Tricks and Tips for Designing a Business in Entrepreneurship" Method. This method of implementation is not only socialization but direct practice inviting the sons and daughters of Turida Village to the Al-Azhar Islamic University Business Incubator as partners of this activity. In this Business Incubator, training is immediately given on marketing strategies through social media, product management and product packaging. With the hope that they will produce the right strategy while at the same time fostering interest in learning, namely strategies to increase creativity, strategies for generating ideas and ideas, not stopping here and becoming an entrepreneurship.